Orthodontic Interceptive Treatment on Obstructive Sleep Apnea Cases - Narmada, Ida Bagus; Winoto, Ervina R; Hakim, Ailsa Marvalodya (Indonesian Journal of Dental Medicine, 2022)
Background: Obstructive sleep apnea (OSA) is a breathing disorder that occurs during sleep and results in decreased or complete cessation of airflow despite attempts to breathe. Specific populations, such as children with certain craniofacial or other genetic syndromes and who are obese have a higher prevalence of OSA than the general population. Craniofacial abnormalities are one of the causes of OSA in the upper airway. Craniofacial morphologies that may predispose to OSA include retrognathia, anterior open bite, midface deficiency, and lower hyoid position. Therefore, interceptive orthodontic treatment in children is needed as one of the treatment options that can be chosen. Purpose: this study aimed to describe the interceptive orthodontic treatments and their effects on OSA cases in children. Review: Interceptive orthodontic treatment has various types depending on how the dentocraniofacial abnormality occurs. Orthodontic treatment aims to reduce the severity of OSA through maxillary and mandibular expansion, thereby increasing air space and airflow. Conclusion: Interceptive orthodontic treatment in pediatric OSA cases include; Rapid Maxillary Expansion, Twin-block, Propulsor Universal Light appliance, Planas appliance modified, Fränkel-II appliance, and BioAJustax oral appliance.